2014
DOI: 10.1097/lgt.0000000000000026
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Religion-Related Factors and Cervical Cancer Screening Among Muslims in Greater Chicago

Abstract: Objective This study aimed to assess rates of Papanicolaou (Pap) testing and associations between religion-related factors and these rates among a racially and ethnically diverse sample of American Muslim women. Materials and Methods A community-based participatory research design was used in partnering with the Council of Islamic Organizations of Greater Chicago to recruit Muslim women attending mosque and community events. These participants self-administered surveys incorporating measures of fatalism, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 34 publications
6
66
5
1
Order By: Relevance
“…Unlike what has been reported in the literature,3240 a high proportion of women (78%) in our pilot study reported ever having a Pap test. However, this finding should be interpreted with caution as it was based on self-report, which has been shown to not be as reliable and accurate a method as objective measures in determining screening rates due to recall, acquiescence, and social desirability biases 4143.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike what has been reported in the literature,3240 a high proportion of women (78%) in our pilot study reported ever having a Pap test. However, this finding should be interpreted with caution as it was based on self-report, which has been shown to not be as reliable and accurate a method as objective measures in determining screening rates due to recall, acquiescence, and social desirability biases 4143.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in agreement with previous findings,39 40 which also reported that cultural or religious beliefs were not a barrier to screening participation. Although in agreement with these findings, Padela et al 41 noted that there was a fatalistic attitude related to negative religious coping, whereby individuals felt that health issues were a penance from God, which resulted in decreased willingness to undergo Pap testing. Therefore, while religious beliefs did not appear to influence acceptability of self-sampling, problems related to fear of the diagnosis should still be addressed when trying to implement self-administered cervicovaginal sampling.…”
Section: Discussionmentioning
confidence: 73%
“…We hypothesized that cultural and religious beliefs, as well as access to screening facilities, might be operating as barriers to CCa screening uptake, as reported in other countries [16][17][18][19][20][21][22][23]. To address this issue, we asked a separate question about possible reasons for not attending for CCa screening.The minimal influence of cultural and religious beliefs on the decision to be screened is a positive finding because these factors can be challenging to modify.…”
Section: Discussionmentioning
confidence: 99%